(untitled) (Global Journal of Human-Social Science, 2012)
The paper examined the act of outright farmland sale in the Ikwerre rural communities to non-agricultural purposes and the increasing decline in agricultural food production The paper argued that the process of farmland sale to non agricultural purposes will further impoverish the people and hamper development We deplored the interview and observation methods of eliciting data The use of Ikwerre dialect became an effective communication tool in gathering data as the rural peasant people are predominantly illiterates The theoretical framework is the Political Economy Approach which served as a study and method The findings are that the increase in sale of farm land to non agricultural activities had destroyed the livelihood of the rural economy and hampered development Also that the decision of communities to share farmland for sale to avert the forceful taken their lands with little or no benefits by the government had created paucity of land scarcity of food communal conflict enmity and death mortality rate